Strengthening Inclusive Learning through Adaptive Physical Education for Madrasah Ibtidaiyah Muhammadiyah Special Program Kartasura Students - Gatot Jariono; Nurhidayat Nurhidayat; Eko Sudarmanto; Rahma Tulloh; Santoso Dwi Anggoro; Rochmadi Rochmadi; Kautsar Rizqi Nursyifa; Adam Sudrajat (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was carried out at Madrasah Ibtidaiyah Muhammadiyah Special Program (MIM SP) Kartasura, Sukoharjo District, Central Java with a focus on strengthening inclusive learning through the Adaptive Physical Education approach. The main issue faced by schools is the limitation of teachers in designing physical activities that are friendly to students with special needs, so assistance is needed to improve pedagogical competence while creating an equal learning atmosphere. The implementation method includes the stage of identifying needs, teacher training, designing adaptive physical learning models, and implementation and evaluation through direct practice in the classroom. A participatory approach is used so that teachers and students are actively involved in the learning process. The results of the mentoring showed an increase in teachers' understanding of the principles of adaptive physical education, the availability of varied and inclusive physical activity designs, and an increase in the involvement of students with special needs in physical activities. The program also fosters regular students' positive attitudes toward their peers with special needs. Thus, this service has succeeded in making a real contribution to strengthening inclusive learning practices in elementary schools through the optimization of adaptive physical education